THE EFFECT OF PEDAGOGICAL COMPETENCE ON TEACHERS’ PROFESSIONAL COMPETENCE, WITH ORGANIZATIONAL CULTURE AS A MODERATING VARIABLE: A STUDY AT SDN MAJALAWANG - Irfan Irfan; Moch Subhan Syarif; Suyudi Suyudi; Hamidah Hamidah; Mutoharoh Mutoharoh (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study was conducted to empirically analyze the influence of pedagogical competence on teacher professional competence, with organizational culture as a moderating variable at Majalawang Elementary School. Pedagogical competence is a basic skill that teachers must possess to manage learning effectively, while professional competence relates to teachers' ability to master learning materials broadly and sustainably. In addition to individual teacher abilities, school organizational culture also plays a crucial role in supporting the improvement of the quality and professionalism of educators. The study used a quantitative approach with a survey method. The study population consisted of all nine teachers at Majalawang Elementary School; thus, the entire population was sampled using a saturated sampling technique. Data collection was conducted using a Likert-based questionnaire structured according to the indicators for each research variable. Data analysis was conducted through validity, reliability, and normality tests, as well as Moderated Regression Analysis (MRA) to determine the influence between variables and the function of organizational culture as a moderating variable. The results showed that pedagogical competence had a positive and significant effect on teacher professional competence. The better a teacher's ability to understand student characteristics, plan lessons, implement teaching and learning activities, and evaluate learning, the higher their professional competence in carrying out their educational duties. Furthermore, organizational culture has been shown to strengthen the relationship between pedagogical competence and teacher professional competence. A harmonious, collaborative organizational culture supported by good communication among school members can increase the effectiveness of the application of pedagogical competence in supporting teacher professionalism. This research implies that strengthening school organizational culture needs to be carried out continuously through increased cooperation, discipline, organizational commitment, and the creation of a positive work environment to support the improvement of teacher competence and professionalism optimally. Thus, schools are expected to be able to create better quality education through the development of professional and competitive human resources